Study of Oxygen Vacancy Diffusion in Yttria-doped Ceria and Yttria-stabilized Zirconia by Statistical Moment Method - Lam, Le Thu; Hung, Vu Van; Hai, Nguyen Thanh (Communications in Physics, 2019)
Oxygen vacancy diffusion in yttria-doped ceria (YDC) and yttria-stabilized zirconia(YSZ) are investigated using statistical moment method, including the anharmonicity effects of thermal lattice vibrations. The expressions of oxygen vacancy-dopant association energy and oxygen vacancy migration energy are derived in an explicit form. Calculation of the vacancy migration energy enable us to evaluate the important role of dopant cation on the oxygen vacancydiffusion. The dependences of the vacancy activation energies and diffusion coefficients in YDC and YSZ systems on dopant concentration are also discussed in detail. The calculated results are in good agreement with the other theoretical and experimental results.